Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian - Yusuf Suhardi; Agustian Burda; Zulkarnaini Zulkarnaini; Arya Darmawan; Laras Oktavia (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2021)
This study examines and determines the effect of the marketing mix (product, price, location, and promotion) on purchasing decisions at SJ supermarkets in Jakarta. The method in this research uses an associative quantitative research strategy. The population is all Sinar Jaya supermarket consumers. With a research sample of 97 respondents from consumers. The sampling technique used was the Non-Probability Sampling technique with the Accidental Sampling method—statistical analysis using multiple linear regression analysis with the help of SPSS version 24.0. The results showed that the product variable had a positive and significant effect on purchasing decisions, the price variable had a positive and significant effect on purchasing decisions, the location variable had no effect on purchasing decisions, and the promotion variable had a positive and significant effect on purchasing decisions. Moreover, the marketing mix (product, price, location, promotion) simultaneously positively and significantly affects purchasing decisions.